2016
DOI: 10.1002/jmri.25381
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3.0T MRI with 3D LAVA sequence and digital subtraction angiography for the assessment of accessory hepatic veins in Budd-Chiari syndrome

Abstract: 4 J. Magn. Reson. Imaging 2017;45:401-409.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…As such, the AHV can be used as an alternative to the HV to facilitate hepatic drainage in individuals diagnosed with BCS. As the AHV is not the primary mediator of hepatic drainage in healthy individuals it is often overlooked, but the hepatic hypertension that develops in individuals with BCS can result in collateral intrahepatic circulation and resultant AHV dilation [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…As such, the AHV can be used as an alternative to the HV to facilitate hepatic drainage in individuals diagnosed with BCS. As the AHV is not the primary mediator of hepatic drainage in healthy individuals it is often overlooked, but the hepatic hypertension that develops in individuals with BCS can result in collateral intrahepatic circulation and resultant AHV dilation [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Balloon dilation is the first treatment to be performed, and stent implantation is an adjunctive measure when repeated angiography shows significant residual stenosis after balloon dilation. When the three major hepatic veins are occluded, the AHVs can undergo compensatory expansion [5,15]. Patients with BCS can be asymptomatic when compensatory expansion of the AHV occurs because the expansive AHV can drain blood from the occlusive major hepatic veins through collateral pathways to the IVC [2,8].…”
Section: Discussionmentioning
confidence: 99%
“…They are usually small and include the inferior right hepatic veins and the caudate veins [2,3]. The AHV is common in patients with BCS, having a reported prevalence that ranges from 54.8 to 78.3% [3][4][5]. The prevalence of AHV obstruction has been reported at 21.8% in patients with BCS involving obstruction of three major hepatic veins [6].…”
Section: Introductionmentioning
confidence: 99%
“…AHV in BCS patients as indicated by a retrospective analysis. Lu et al (32) suggested that LAVA sequence is able to detect more AHVs than DSA. In addition, MRA clearly reveals the opening direction of AHV and the angle between AHV and distal vena cava, which have practical value for interventional therapy (33).…”
Section: Discussionmentioning
confidence: 99%